2005
DOI: 10.1016/j.cardiores.2004.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin prevents the acute myocardial inflammatory response induced by ischemia/reperfusion via induction of AP-1

Abstract: Collectively, these findings indicate that EPO can ameliorate the myocardial inflammatory response in both in vitro and in vivo models of I/R. This beneficial effect of EPO is mediated by eNOS-derived NO via a PI3-kinase-dependent activation of AP-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
82
1
7

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(97 citation statements)
references
References 43 publications
7
82
1
7
Order By: Relevance
“…As mentioned above EPO in various studies has been reported to exert number of important actions like anti-oxidative (Genc et al, 2004;Signore et al, 2006;Xue et al, 2007;Wang et al, 2009), neuroprotective (Morishita et al, 1997;Lewczuk et al, 2000;Siren et al, 2001b), neurotrophic (Viviani et al, 2005) effects and a vital role in hippocampal LTP (Adamcio et al, 2008;El-Kordi et al, 2009). EPO has also shown to exert potential anti-inflammatory actions (Rui et al, 2005;Liu et al, 2006) and role of inflammation in the pathobiology of AD is well documented (Granic et al, 2009;Salminen et al, 2009). Therefore, with support from literature and data in hand it may be proposed that EPO mediated beneficial effect in STZ (i.c.v.…”
Section: Discussionmentioning
confidence: 96%
“…As mentioned above EPO in various studies has been reported to exert number of important actions like anti-oxidative (Genc et al, 2004;Signore et al, 2006;Xue et al, 2007;Wang et al, 2009), neuroprotective (Morishita et al, 1997;Lewczuk et al, 2000;Siren et al, 2001b), neurotrophic (Viviani et al, 2005) effects and a vital role in hippocampal LTP (Adamcio et al, 2008;El-Kordi et al, 2009). EPO has also shown to exert potential anti-inflammatory actions (Rui et al, 2005;Liu et al, 2006) and role of inflammation in the pathobiology of AD is well documented (Granic et al, 2009;Salminen et al, 2009). Therefore, with support from literature and data in hand it may be proposed that EPO mediated beneficial effect in STZ (i.c.v.…”
Section: Discussionmentioning
confidence: 96%
“…Myocardial Inflammation-As an index of polymorphonuclear neutrophil infiltration, myeloperoxidase activity in the myocardium was determined by measuring hydrogen peroxide-dependent oxidation of 3,3Ј, 5,5Ј-tetramethylbenzidine as described previously (33). To quantify the mast cells in the heart, cardiac tissue sections were stained with 0.02% toluidine blue in 0.25% acetic acid (pH 2.0 -2.5).…”
Section: Capn4mentioning
confidence: 99%
“…Western blot. Phosphorylated and total protein of interest in endothelial cells was assessed by Western blot as previously described (39,40). In brief, after challenge, the cells were harvested in lysis buffer, sonicated, and 5 g of cell protein was resolved by 10% SDS-PAGE.…”
Section: Assaysmentioning
confidence: 99%